Simulation study of an advanced control strategy for a PUMA like robot manipulator - Muhammed Mansor Ben Karsa, Muftah Naji (2005)
The work of this project concerned with the presentation of an integrated mathematical model of the robot manipulator. The model of the system considered comprises the mechanical part of the robot manipulator, the actuators, as well as the gear trains. The formulation results in nonlinear time varying state equations, which represent a more realistic model of the robotic system. Decomposition and reduce the integrated model of the robot manipulator into a system with bounded uncertainties is presented. The Integral Sliding Mode Controller applied to a three degree of freedom PUMA like robot manipulator actuated by DC motors. It is shown that the robot manipulator utilizing the presented controller is practically stable and tracks a reference trajectory if a given sufficient condition is satisfied. The controller performance is evaluated through the simulation using MATLAB/SIMULINK. The performance of Integral Sliding Mode Controller is to be compared with an Independent Joint Linear Control